Octave-generalized analysis of chord progressions: Diatonic/fifth relations, missing fundamentals, completion tones. Issue 1 (1st January 2021) - Parncutt, Richard; Reisinger, Daniel
Abstract : In a representative historical database of musical scores, a sonority was defined at every onset in any voice. For eight trichords—major (047), minor (037), suspended (027), diminished (036), 015, 045, 025, 035—immediately preceding and following sonorities were analysed. Chroma prevalence profiles depended surprisingly little on century or temporal position—especially for major/minor trichords (cf. Krumhansl's key profiles). Profiles for nine non-chord chromas per trichord were influenced more strongly by diatonic scales and 5th relationships than missing fundamentals (roots) or completion tones (tones that complete familiar tetrachords) according to predictions of simple models.